Bacteriocin-producing Enterococcus faecalis KT2W2G isolated from mangrove forests in southern Thailand: Purification, characterization and safety evaluation. (August 2015) - H-Kittikun, Aran; Biscola, Vanessa; El-Ghaish, Shady; Jaffrès, Emmanuel; Dousset, Xavier; Pillot, Guillaume; Haertlé, Thomas; Chobert, Jean-Marc; Hwanhlem, Noraphat
Abstract: The aim of this work was to purify and characterize the bacteriocin produced by Enterococcus faecalis KT2W2G isolated from the mangrove forest in southern Thailand, in order to evaluate its potential as a new food protective agent. The active peptide from the cell-free supernatant of Ent. faecalis KT2W2G was purified in 4 steps: (i) precipitation with 70% saturated ammonium sulfate, (ii) elution on a reversed phase cartridge (Sep-Pak C8 ) using different concentrations of acetonitrile, (iii) cation-exchange chromatography and (iv) final purification by reversed phase-HPLC on a C8 column. Each purification step increased the specific activity and reduced the amount of contaminating non-bacteriocin proteins. The specific activity of purified bacteriocin was 13, 470.53 AU/mg of protein, which corresponded to a 48.10-fold increase. Tricine–SDS-PAGE of the purified bacteriocin gave molecular weight ranging between 3.5 and 6.5 kDa. The activity of the partially purified bacteriocin was unaffected by pH (2.0–12.0) and thermostable, but was sensitive to proteolytic enzymes. This bacteriocin maintained full stability after storage at −20, 4 and 37 °C for 2 months. It was stable when incubated for 1 month at 4 °C in 0–30% NaCl. Inhibitory spectrum of this bacteriocin showed a wide range of activities against other LAB, food-spoilage and food-borne pathogens. Ent. faecalis KT2W2G was sensitive to kanamycin, tetracycline and vancomycin but resistant to ampicillin, gentamicin and penicillin. PCR amplification demonstrated that Ent. faecalis KT2W2G does not harbor virulence genes cylA, cylB and esp but has virulence genes ace, asa1 and efaAfs. The bacteriocin and its producing strain may find application as bio-preservatives for reduction of food-spoilage and food-borne pathogens in food products. Highlights: KT2W2G is a bacteriocin-producing strain isolated from brackish water. We successfully purify and characterize the bacteriocin produced by strain KT2W2G. Bacteriocin KT2W2G was very stable under various conditions. Bacteriocin KT2W2G showed activities against food-spoilage and food-borne pathogens. Bacteriocin KT2W2G may be useful as a bio-preservative in food products.